2020
DOI: 10.1016/j.jconrel.2020.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Advances and limitations of drug delivery systems formulated as eye drops

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
125
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(146 citation statements)
references
References 148 publications
0
125
0
2
Order By: Relevance
“…The fitting could be perfect at a small time region or at a large time region but no at the whole time domain. The type of the deviation led to adding another exponential term in Equation (6). The proposed equation has the form:…”
Section: Modeling Of Drug Release Datamentioning
confidence: 99%
“…The fitting could be perfect at a small time region or at a large time region but no at the whole time domain. The type of the deviation led to adding another exponential term in Equation (6). The proposed equation has the form:…”
Section: Modeling Of Drug Release Datamentioning
confidence: 99%
“…Besides its lower mucoadhesive strength, at neutral pH, CS has some additional limitations such as a low water solubility and low swelling properties. For example, the mucoadhesive strength of neat CS was estimated to 0.34 N/cm 2 [62], while PAA (Carbopol 934) had a much higher mucoadhesive strength (about 0.51 N/cm 2 ) [63]. To overcome these problems, CS has been modified with appropriate monomers, which have additional reactive groups to ensure mucoadhesion at pH 7 [64][65][66].…”
Section: Mucoadhesion Of Cs and Its Derivativesmentioning
confidence: 99%
“…Moreover, only a small volume (approximately 30 μL) of eye drop formulation can be instilled in the eye. As a result, concentrated solutions have to be administered, and frequent instillations are necessary to reach a therapeutic result [2,[9][10][11]. Systemic delivery is an alternative delivery method, yet not an ideal one as other limitations arise: first-pass metabolism, side effects, blood-ocular barriers, low eye vascularization, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, gelatin can be applied in different forms (e.g., hydrogels) for the repair of various ocular diseases such as focal corneal wounds [87]. Gelatin nanoparticles as a DDS show merits including appropriate compatibility to ocular compartments, very low antigenicity, good mucoadhesive properties, good stability, effective lowering of the IOP, high drug bioavailability, and a lack of irritation [88][89][90]. In 2016, Mahor et al reported the use of cationic gelatin nanoparticles loaded with moxifloxacin as an effective ocular DDS in the corneal layer [91].…”
Section: Gelatinmentioning
confidence: 99%